For‐Profit Institutions and Student Veteran Data. Issue 171 (May 2017) - Jones, Kevin C.; Fox Garrity, Bonnie K.
Abstract : This chapter explores the lack of data about student veterans and reasons this lack of data raises particular concerns about for‐profit institutions, which enroll a large percentage of student veterans.